On the relation between the red sprites and the transients in the ELF band - ONDRÁŠKOVÁ, Adriena; ŠEVČÍK, Sebastián; KOSTECKÝ, Pavel; TÓTH, Juraj; KYSEL, Róbert (Contributions to Geophysics and Geodesy, 2010)
Under favourable conditions sprites appear above large storms. Long continuingcurrent in tens of ms in the parent +CG stroke radiates electromagnetic energy alsoin the Schumann resonance (SR) band. Optical and Extremely Low Frequency (ELF)observations at the Astronomical and Geophysical Observatory (AGO) near Modra areanalyzed to find these two effects associated with +CG discharges. Since April 2007dozens of sprites have been captured by automated all-sky TV system at AGO. A majority(77%) of the optical transient events are accompanied with the transients in the SRband. No ELF counterparts are found for 23% of the captured sprites. Our observationsare compared with similar observations in Sopron and Nagycenk (NCK). Example of theoptical frames, the associated ELF time plot and the Fourier as well as dynamic spectrumare presented for one of the events simultaneously observed at AGO and NCK.